URGENSITAS MANAJEMEN PERUBAHAN PENDIDIKAN ISLAM DI ERA GLOBALISASI - Moh. Hasan Firghol Muttaqien Firghol; Dika Tripitasari; Muhammad Zaironi (STKIP Pesisir Selatan, 2026)
Objective: Change occurs in various walks of life, including in the world of education. The main triggers for change come from within or outside an organization. On the other hand, the driving factors for change in educational institutions are the influence of globalization, the development of science and technology (IPTEK), and the ever-expanding flow of information. In this era, technological progress is inevitable, as it goes hand in hand with the development of science. This study aims to explain the urgency of educational change management in the era of globalization. This type of research is qualitative with a librarian research approach. The research data consists of data on the urgency of change management in Islamic educational institutions from primary sources such as books and several relevant journals. Based on the research results, it was found that the urgency of Islamic educational change management in the development of Islamic educational institutions is crucial and cannot be ignored. In a constantly changing and complex context, change management plays a key role in ensuring that educational institutions remain relevant, high-quality, and in accordance with Islamic values.